Case Study: Enhancing the Learning Experiences of BAME Students at a University: The University Role. Issue 1 (4th January 2022) - Lim, Hyun-Joo
Abstract : This case study examines the role of a university and academics in improving the learning experiences of BAME students, drawing on student-led participatory action research with Social Sciences BAME students at Bournemouth University (BU henceforth) between 2018-2020. The paper seeks to illuminate the critical role of the university by focusing on three inter-related facets at macro, meso and micro levels (Bronfenbrenner, 1979 ): financial and temporal/spatial support for students; collaboration between academic staff at departmental and faculty levels to address any issues that arose from student meetings; and its consequential impact on student wellbeing, self-worth and their overall engagement in their learning. I argue that to achieve the utmost improvement in BAME students' learning experiences, these different levels of the support system need to work together. I further argue that maximising the potentiality of 'ethnic capital' (Modood, 2004 ) could be a powerful resource that could bring significant changes to the experiences of BAME students and subsequent outcomes of their learning during and after university.